Handbook for Philippine museums - Peralta, Jesus T. 1932- (Manila National Commission for Culture and Arts, NCCA Committee of Museums, 1993)
Purpose: A reference guide "for museum workers in the Philippines." : "prepared for the use of small museums with limited conservation facilities to enable the curator to confront daily problems, and to institute emergency measures."
Content/s: Museum (definition, characteristics and recourses). Collection. Documentation. Physical Facilities. Storage System. Exhibition. Conservation. Pollutants. Temperature. Humidity. Light. Emergency Conservation. Security. Fumigation with Paradichlorobenzene (poison).
"Published on the occasion of the Third Annual Museum Congress, Museum and Gallery Month October 1993."
Keywords: Museum techniques -- Philippines -- Handbooks, manuals, etc